INVESTIGATING THE USE OF INDIGENOUS MICROBIAL ISOLATES FOR BIOCONTROL OF LEAFSPOT DISEASE IN SOLO- GOLD SWEET POTATO - Alfonso, O. C.; Afuape, S. O.; Oyekanmi, B. A.; Abimbola, O. O.; Salawu, I. A.; Salami, A. O. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study explored the use of indigenous microbial isolates for biocontrol of leafspot disease and growth promotion in Solo-gold sweet potato by isolating microorganisms from tissues of a healthy sweet potato variety and assessing the effectiveness of the isolates in suppressing leafspot disease on Solo-gold sweet potato. The treatment consisted of leaf, stem and root parts of a healthy sweet potato variety (Ex-igbariam), collected for fungal and bacterial isolation in the laboratory. The isolates were prepared into suspensions and inoculated into leafspot infected Solo-gold plant in the screenhouse. Isolates inoculation was carried out singly and, in all combinations. Data on the disease incidence, severity, and other growth parameters were collected at 6, 8, 10, and 12 weeks after planting. Data collected were subjected to analysis of variance (ANOVA) and significant means were compared using Fisher’s LSD at 5% level of probability. Five pure cultures (two bacteria and two fungi) were isolated from the healthy sweet potato parts. The results showed that, isolates inoculation effect on Solo-gold differed significantly (P < 0.01). While some isolates inhibited leafspot expression on Solo-gold, certain isolates significantly suppressed the disease and enhanced the plant growth compared to the controls. The findings of this study underscore the potential of indigenous microbial isolates as biocontrol agents for managing leafspot disease and improving the growth of Solo-gold sweet potato variety, contributing to the development of sustainable and environmentally friendly strategies for managing diseases in agricultural production.